2007
DOI: 10.1080/00365540600951309
|View full text |Cite
|
Sign up to set email alerts
|

Fatal bacterial meningitis after spinal anaesthesia

Abstract: A 37-y-old male was admitted to the ICU because of meningitis and respiratory failure with epileptic seizures. Spinal fluid grew Streptococcus salivarius. Prior to presentation the patient underwent surgical excision of a chronic toe ulcer, performed under spinal anaesthesia, which raised the suspicion of iatrogenic origin of the disease. The clinical situation deteriorated over the following d and the patient died from multi-organ failure. Careful hygiene measures are needed to prevent such a severe complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…S. salivarius is a commensal member of the oral mucosa, and many cases have been tracked to the oral microbiome of a healthcare provider performing a procedure on the case patient. 19,32,36 This suggests that droplet transmission or contamination of sterile equipment by the operator is an important mechanism for inoculation. Thus, strict practices of aseptic technique S. salivarius meningitis during these procedures and use of a facemask in accordance with guidelines as published by the Healthcare Infection Control Practices Advisory Committee and American Society of Regional Anesthesia and Pain Medicine will be important to limiting the incidence of these events.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…S. salivarius is a commensal member of the oral mucosa, and many cases have been tracked to the oral microbiome of a healthcare provider performing a procedure on the case patient. 19,32,36 This suggests that droplet transmission or contamination of sterile equipment by the operator is an important mechanism for inoculation. Thus, strict practices of aseptic technique S. salivarius meningitis during these procedures and use of a facemask in accordance with guidelines as published by the Healthcare Infection Control Practices Advisory Committee and American Society of Regional Anesthesia and Pain Medicine will be important to limiting the incidence of these events.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…4,36 Complications occurred in five patients, one of whom died. These complications included fatigue and decreased concentration in a 35-year-old female who sustained S. salivarius meningitis from epidural anesthesia.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…This is attributable to the possibility that subarachnoid or dural puncture can spread infection to the epidural or intrathecal space in patients with a systemic infection [27]. Individual cases of these CNS infections have been reported [1,13]; however, the limited and at times conflicting data available do not provide a convincing argument against the use of neuraxial anesthesia in patients with infection. In a retrospective series in Sweden involving 1,260,000 spinal and 450,000 epidural anesthetics performed during a decade, Moen et al [22] reported epidural abscess in 13 patients and meningitis in 29.…”
Section: Introductionmentioning
confidence: 99%
“…This is a very important finding, especially since in available literature we found very rare similar cases (16,17). Halaby et al (17) reported a case of fatal bacterial meningitis after spinal anesthesia.…”
Section: Discussionmentioning
confidence: 73%
“…Of the several pos- sible mechanisms for the pathogenesis of infections, given the nature of the outbreak (rapid onset post-surgery, complexity of the surgeries, severity of disease) a direct intravenous bolus of bacteria was suspected. This could have occurred if one or more of the following were contaminated: medications used during surgery, instruments, skin overlaying the site of surgery, or the hands of personnel performing the procedure (16,17). Extensive environmental microbiological investigations were performed.…”
Section: Discussionmentioning
confidence: 99%